Effect of root growth regulator and bio fertilizer on growth of grafted cuttings of Cinchona ledgeriana Moens clone Cibeureum 5 in nursery - Herland Wijaya Kusumo; Joko Santoso (Jurnal Penelitian Teh dan Kina, 2014)
An experiment to determine the best concentration of root growth regulator and bio fertilizer dosage to increase the growth of grafted cuttings of Cinchona spp. has been conducted in the shading of cuttings seedling Research Institute of Tea and Cinchona, Gambung from, April to June 2013. ExpeÂrimental design used was a randomized block design (RBD) with sixteen treatments in two replications. The treatments were: Root Growth Regulator (RGR) consisted of four treatments; 0, 25, 50, 75 mg/mlcombined with Bio FerÂtilizer consisted of four dosages: 0; 0,5; 1,0; 1,5 mg/plant. The results showed that root growth regulator combined with bio-fertilizer had good effect on first occurrence of root, root length and root volume. Root Growth Regulator of 50 mg/ml + bio-fertilizer 0 g/plant gave best effect on root length and root volume.